Don't judge a book by its cover: The role of intergroup contact in reducing prejudice in conflict settings - Surya Nath Maiti; Debayan Pakrashi; Sarani Saha; Russell Smyth (Global Labor Organization (GLO), 2020)
We study the potential for pleasant and cooperative contact to reduce preconceived prejudice between religious groups in the context of India. We randomly assign Hindus and Muslims into groups, in which they interact over the course of a week-long vocational training program. We find that intergroup contact reduces the prejudice of both Hindu and Muslim participants toward members of the other religion one week after the training program finished. While we find that most of the positive effect of intergroup contact on reducing prejudice dissipates after six months, the baseline results for Hindu attitudes toward Muslims are persistent.
Keywords: C93; J15; Z12; Z18; 330; religion; attitude; prejudice; vocational training